Electricity : a question and answer book - Richardson, Adele, 1966- (Mankato, Minn. : Capstone Press, 2006)
Introduces electricity and its generation, components, movement, and functions in a question and answer format, and includes "fast facts" and step-by-step instructions for building a circuit.
Includes bibliographical references (p. 31) and index.
Horn Book
Library Media Connection
Science and Children (N.S.T.A.)
4.6
3-6
Keywords: Electricity -- Juvenile literature; Electricity; Electricity